2021
DOI: 10.1002/mabi.202100319
|View full text |Cite
|
Sign up to set email alerts
|

Application of Temporary, Cell‐Containing Alginate Microcarriers to Facilitate the Fabrication of Spatially Defined Cell Pockets in 3D Collagen Hydrogels

Abstract: Mimicking the complexity of natural tissue is a major challenge in the field of tissue engineering. Here, a facile 2‐step fabrication method to prepare 3D constructs with distinct regions of high cell concentrations and without the need for elaborate equipment is proposed. The initial incorporation of cells in a sacrificial alginate matrix allows the addition of other, cell relevant biopolymers, such as, collagen to form a spatially confined, interpenetrating network at the microscale. A layered structure at t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 75 publications
0
2
0
Order By: Relevance
“…Thankfully, in another investigation, cells were successfully encapsulated inside the holes of the porous collagen scaffolds using transient calcium alginate microcarriers (650 ± 42 μm) bear-ing placeholders. [16] Tragically, the central tissue of the 8.5 mmdiameter globules may necrotize because the cells there may be undernourished and hypoxic. Additionally, the excessive collagen construction time that results in an uneven distribution of cells in the collagen scaffold hinders spatio-controlled heterogeneous cell coculture.…”
Section: Introductionmentioning
confidence: 99%
“…Thankfully, in another investigation, cells were successfully encapsulated inside the holes of the porous collagen scaffolds using transient calcium alginate microcarriers (650 ± 42 μm) bear-ing placeholders. [16] Tragically, the central tissue of the 8.5 mmdiameter globules may necrotize because the cells there may be undernourished and hypoxic. Additionally, the excessive collagen construction time that results in an uneven distribution of cells in the collagen scaffold hinders spatio-controlled heterogeneous cell coculture.…”
Section: Introductionmentioning
confidence: 99%
“…Functional polymers based on cyclodextrin have been DOI: 10.1002/macp.202200444 designed and studied reported in time highlighting the enhancement of encapsulation and release ability, the improvement of mechanical characteristics, biodegradability, [1][2][3] Alg is an anionic polysaccharide that is generally used in biomedical and pharmaceutical applications due to its biodegradability, nontoxicity, biocompatibility, low immunogenicity, etc. [4][5][6][7] A number of studies reported on the synthesis of Alg modified with cyclodextrin units. [8][9][10] Studies in this field have shown that, the binding of CD to the Alg chain can generate large supramolecular assemblies through host-guest interactions and can improve the properties of polymeric systems which has been exploited in pharmaceutical domain.…”
Section: Introductionmentioning
confidence: 99%